Cost-Effectiveness of Nivolumab Immunotherapy vs. Paclitaxel or Docetaxel Chemotherapy as Second-Line Therapy in Advanced Esophageal Squamous Cell Carcinoma in China - Lin, Ying-tao; Liu, Tian-xiu; Chen, Jian; Wang, Chang; Chen, Ying (Frontiers in Public Health, 2022)
This study aimed to evaluate and compare nivolumab's cost-effectiveness with chemotherapy in patients with advanced esophageal squamous cell carcinoma from the Chinese healthcare system perspective. To this end, the researchers utilized a partitioned survival model with three mutually exclusive health stages. The characteristics of the patients used as inclusion and exclusion criteria in this model were the same as those used for patients with advanced esophageal squamous cell carcinoma in the ATTRACTION-3 study. The ATTRACTION-3 trial, which took place between January 7, 2016 and November 12, 2018, also yielded important clinical data. Data on medical and economic preferences were collected from real-world clinical practices. Costs, quality-adjusted life years, and incremental cost-effectiveness ratio were calculated for the two therapy options. The model uncertainty was investigated using a deterministic and probabilistic sensitivity analysis. When compared to chemotherapy, nivolumab was linked with an increase of 0.28 quality-adjusted life years with an increased cost of US$ 36,956.81 per patient in the base case analysis of a hypothetical sample of 419 patients. The incremental cost-effectiveness ratio in the deterministic sensitivity analysis was US$ 132,029.46/quality-adjusted life year, with a 48.02% probability of being cost-effective at willingness-to-pay thresholds of US$ 132,029.22/quality-adjusted life year. The incremental cost-effectiveness ratio remained greater than US$ 80,000/quality-adjusted life year in the deterministic sensitivity analyses. To be more cost-effective and remain below the threshold of 37,653 US$/quality-adjusted life year, which the Chinese population can afford, nivolumab's price would have to be lowered sharply by 53.50%. Nivolumab is clinically beneficial but not cost-effective when compared to chemotherapy. A substantial reduction in nivolumab's drug acquisition cost would be necessary to make it cost-effective for immunotherapy.